KAJIAN KEBIJAKAN MODAL SOSIAL DALAM MENYELESAIKAN KONFLIK TAMBANG PADA MASYARAKAT PESISIR - Fitriansyah (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2020)
Social conflicts always occur because of interests in people's lives. Likewise, what happens to coastal communities as a result of negative excesses in carrying out mining activities, so that this environmental condition is not managed wisely and can cause conflicts that are detrimental to the parties concerned. This writing aims to analyze and examine the application of social capital as a policy in resolving conflicts. The qualitative descriptive method examines some literature related to the handling of social conflicts, one of which is developing the existing social capital in society. Reference to social capital developed by the government through the Ministry of Social Affairs of the Republic of Indonesia as a policy for resolving social conflicts, with the assumption that social capital can generate collective consensus in society to answer problems that lead to social conflict. The conclusion of this conclusion shows that the development of social capital through social harmony programs is functionally not fully utilized, because of the various connecting services. So we need the right solutions and strategies in developing these policies.